ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BERBASIS BAGI HASIL PADA PERBANKAN SYARIAH DI INDONESIA PERIODE 2010-2014 - Asri, Aida Sania; Syaichu, Muhamad (Diponegoro Journal of Management, 2016)
Islamic banking is a financial institution that serves as an intermediary between the parties that have surplus funds and those who need funds. As intermediary institution, Islamic bank perform its role by channeling funds for financing. There are several products of financing that provided by Islamic bank, one of them is profit and loss sharing based of financing. The attempt of Islamic bank in channeling its funds for financing was not apart from the risks, therefore good management and control are needed. Islamic bank should observe the factors that may affect on financing. The purpose of this study was to analyze the factors that influence profit and loss sharing based of financing of Islamic bank.The population in this study was Islamic commercial banks in Indonesia, which consists of 12 banks. The samples used are selected using purposive sampling technique and there are 4 banks that meet the criteria. The data used in this study are secondary data that obtained from quarterly financial reports of Islamic bank during the period of 2010-2014, and the number of observation points is 100. The method of data analysis used in this study is multiple linear regression analysis with significant level of 5%.The results showed that simultaneously, the five independent variables include equivalent rate, FDR, CAR, NPF, and SWBI are significantly influence to profit and loss sharing based of financing. Partially, SWBI has positive significant effect on profit and loss sharing based of financing and CAR influence significantly negative to profit and loss sharing based of financing, while equivalent rate, CAR and NPF didn’t influence to profit and loss sharing based of financing. Result of regression estimation show that the predictive ability of the model was 70.2%, while the remaining 29.8% was influenced by other factors outside the model.